Co-Expression and Combined Prognostic Value of CSPG4 and PDL1 in TP53-Aberrant Triple-Negative Breast Cancer - Hu, Zhe-Yu; Zheng, Chanjuan; Yang, Jianbo; Ding, Siyu; Tian, Can; Xie, Ning; Xue, Lian; Wu, Muyao; Fu, Shujun; Rao, Zhouzhou; Price, Matthew A.; McCarthy, James B.; et al. (Frontiers in Oncology, 2022)
Background: In triple-negative breast cancer (TNBC), PDL1/PD1-directed immunotherapy is effective in less than 20% of patients. In our preliminary study, we have found CSPG4 to be highly expressed together with PDL1 in TNBCs, particularly those harboring TP53 aberrations. However, the clinical implications of co-expressed CSPG4 and PDL1 in TNBCs remain elusive. Methods: 85 advanced TNBC patients treated in Hunan Cancer Hospital between January 2017 and August 2019 were recruited. The expressions of CSPG4 and PDL1 in TNBC tissues were investigated using immunohistochemistry (IHC).The RNA-seq dataset from the TCGA-BRCA project was further used to analyze the mRNA expression of CSPG4 and PDL1 in TP53-aberrant TNBCs. Cox proportional hazards model and Kaplan-Meier curves with Logrank test was used to analyze the effects of CSPG4 and PDL1 on survival. TNBC cell lines were further used to investigate the molecular mechanism that were involved. Results: TP53 aberrations occurred in more than 50% of metastatic TNBCs and were related to higher tumor mutation burden (TMB). In TCGA-BRCA RNA-seq dataset analysis, both CSPG4 and PDL1 levels were high in TNBCs, especially in TP53-aberrant TNBCs. IHC assay showed nearly 60% of advanced TNBCs to be CSPG4-positive and about 25% to be both CSPG4-positive and PDL1-positive. The levels of CSPG4 and PDL1 were high in TNBC cell lines as revealed by flow cytometry and immunoblotting compared with non-TNBC cells. Univariate Cox regression analysis indicated that CSPG4 positivity was a significant risk factor for progression-free survival in metastatic TNBCs, with a hazard ratio (HR) of 2.26 (P = 0.05). KM curves with Logrank test also identified high level of CSPG4 as a significant risk factor for overall survival in advanced breast cancers in TCGA-BRCA samples (P = 0.02). The immunoblotting assays showed that EMT-related pathways were involved in CSPG4-mediated invasion. Conclusions: CSPG4 expression level is associated with PDL1 positivity in TP53-aberrant TNBC cells. Patients with CSPG4 expression have poor treatment response and poor overall survival. Co-expressed CSPG4 and PDL1 may have an important prognostic value and provide new therapeutic targets in TNBC patients. CSPG4 might mediate tumor invasion and PDL1 overexpression through EMT-related pathway.